L'État de droit démocratique - Jouanjan, Olivier (2019)
In Europe, democracy has a bright future. Not one democratic mechanism, however direct, cannot guarantee direct democracy. Therefore, the theory of populism by theoretician Carl Schmitt is analyzed « thoughts on Schmitt against Schmitt : Ernst-Wolfgang Böckenförde“. Furthermore, the democratic myth is discussed and its ideology. The state of rule of law of modern democracy and the two faces of modern democracy are analyzed. The need to participate in civil society in administrative control is stressed. The relation of the tension between democracy and rule of law is observed. The need to consider the concept of considering modern democracy in relation to the idea of rule of law, democracies under conditions of modern politics on the basis of which Böckenförde, referring to Hegel, calls the problem „division “are emphasized. It is precisely from this problem that Böckenförde shows that modern democracy can only be representative. Representation is a fundamental principle of the rule of law while representation means a system of formation necessary for expressing the political will of the people. Every formation of the collective process means the introduction of standards of procedure, significant guarantees and formal conditions of this process.
U Europi demokracija ima svijetlu budućnost. Nijedan demokratski mehanizam, koliko god bio izravan, ne može jamčiti izravnu demokraciju. Stoga se teorija populizma teoretičara Carla Schmitta analizira «misli o Schmittu protiv Schmitta: Ernst-Wolfgang Böckenförde». Nadalje, raspravlja se o demokratskom mitu i njegovoj ideologiji. Analizira se stanje vladavine prava moderne demokracije i dva lica suvremene demokracije. Naglašena je potreba sudjelovanja u civilnom društvu u upravnoj kontroli. Promatra se odnos napetosti između demokracije i vladavine prava. Naglašena je potreba razmatranja koncepta promišljanja moderne demokracije u odnosu na ideju vladavine prava, demokracija u uvjetima moderne politike na temelju kojih Böckenförde, pozivajući se na Hegela, naziva problem „podjele“. Upravo iz tog problema Böckenförde pokazuje da moderna demokracija može biti samo reprezentativna. Zastupanje je temeljno načelo vladavine prava, dok reprezentacija znači sustav formiranja potreban za izražavanje političke volje ljudi. Svako formiranje kolektivnog procesa znači uvođenje proceduralnih standarda, značajna jamstva i formalne uvjete tog procesa.
En Europe, la démocratie a un avenir radieux. Aucun mécanisme démocratique, même direct, ne peut garantir la démocratie directe. Par conséquent, la théorie du populisme du théoricien Carl Schmitt est analysée «Réflexions sur Schmitt contre Schmitt: Ernst-Wolfgang Böckenförde». En outre, le mythe démocratique est discuté et son idéologie. L'état de droit de la démocratie moderne et les deux visages de la démocratie moderne sont analysés. La nécessité de participer à la société civile au contrôle administratif est soulignée. La relation de tension entre démocratie et Etat de droit est observée. La nécessité de considérer le concept de considérer la démocratie moderne en relation avec la notion d'état de droit, les démocraties dans les conditions de la politique moderne sur la base desquelles Böckenförde, se référant à Hegel, appelle le problème "division" sont soulignés. C'est précisément à partir de ce problème que Böckenförde montre que la démocratie moderne ne peut être que représentative. La représentation est un principe fondamental de l’état de droit, tandis que la représentation signifie un système de formation nécessaire pour exprimer la volonté politique du peuple. Chaque formation du processus collectif implique l’introduction de normes de procédure, de garanties importantes et de conditions de forme de ce processus.
Bibliografske bilješke uz tekst.
Summary ; Sažetak ; Resume.
Keywords: Vladavina prava -- Demokracija